2012
DOI: 10.1103/physrevlett.108.257006
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle Dynamics and Phonon Softening in FeSe Superconductors

Abstract: Quasiparticle dynamics of FeSe single crystals revealed by dual-color transient reflectivity measurements (∆R/R) provides unprecedented information on Fe-based superconductors. The amplitude of the fast component in ∆R/R clearly gives a competing scenario between spin fluctuations and superconductivity. Together with the transport measurements, the relaxation time analysis further exhibits anomalous changes at 90 and 230 K. The former manifests a structure phase transition as well as the associated phonon soft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 28 publications
(35 reference statements)
6
76
0
2
Order By: Relevance
“…From high temperature to low temperature, dramatically increases beginning at T c (36 K) and roughly saturates below 25 K. also has a peak at T c . These features were similar to those of quasiparticle relaxation due to the SC gap in other iron-based superconductors26293046. Although iron-based superconductors have multiple bands with different SC gaps, a temperature-dependent one-gap system based on the Rothwarf-Taylor (RT) model was still adequate to estimate the SC gap size for FeSe46, LiFeAs26, Ba 0.6 K 0.4 Fe 2 As 2  30, and SmFeAsO 0.8 F 0.2  29.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…From high temperature to low temperature, dramatically increases beginning at T c (36 K) and roughly saturates below 25 K. also has a peak at T c . These features were similar to those of quasiparticle relaxation due to the SC gap in other iron-based superconductors26293046. Although iron-based superconductors have multiple bands with different SC gaps, a temperature-dependent one-gap system based on the Rothwarf-Taylor (RT) model was still adequate to estimate the SC gap size for FeSe46, LiFeAs26, Ba 0.6 K 0.4 Fe 2 As 2  30, and SmFeAsO 0.8 F 0.2  29.…”
Section: Resultssupporting
confidence: 75%
“…It was reported that the decay rate of the quasiparticles due to the SC gap varies with optical pump fluence55. In our temperature-dependent measurements, the optical pump fluence was 5 μJ/cm 2 below 50 K, which was reasonably low compared with previous experiments on iron-based superconductors252629304655. For enhancement of the signal to noise ratio, the optical pump fluence was 10 μJ/cm 2 for measurements above 50 K because they are in the linear region.…”
Section: Methodssupporting
confidence: 46%
“…21 The very well characterized samples were from the same series as in previous investigations. 21,22 The present samples composition is FeSe 0.96 . Raman spectra were measured on freshly cleaved surfaces in a quasi-back scattering configuration using a λ = 532.1 nm solid-state laser.…”
Section: Methodsmentioning
confidence: 71%
“…[7][8][9][10] In this respect, as the structurally simplest Fe-based superconductor, FeSe has unexpectedly emerged in the frontier of Fe-based superconductivity research. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Up to date, few consensuses have been reached on either the electronic structure of FeSe or its nematic and superconducting mechanisms. For example, very recent angle-resolved photoemission spectroscopy (ARPES) has indicated a small Fermi surface (FS) above T s that cannot be reproduced by density functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%